2018
DOI: 10.4102/jamba.v10i1.476
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and vulnerability discourse by students at a South African university

Abstract: Climate change is expected to pose grave consequences to communities around the world. It is predicted that many people, mostly in the developing world, will experience shortages of water and food as well as numerous health-related effects because of climate change. Therefore, rigorous global action is needed to enable developing countries to adapt to the effects of climate change. Universities play a pivotal role in addressing these issues and their impacts through research and technological innovations. Henc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 19 publications
3
26
0
Order By: Relevance
“…Climate change impact studies, although they are still uncertain on the frequency and severity of adverse weather events, have shown that the effects are significant for low-input farming systems, such as subsistence farming in marginal areas and because of socio-economic, demographic and policy trends have the least capacity to adapt to changing climatic conditions (Mutekwa 2009). Climate change is a serious threat to development and poverty reduction efforts in Africa (Mugambiwa & Dzomonda 2018; Mugambiwa & Tirivangasi 2017). The continent is facing various health risks associated with climate change and threaten to reverse development efforts and subject the continent to long-term poverty.…”
Section: Introductionmentioning
confidence: 99%
“…Climate change impact studies, although they are still uncertain on the frequency and severity of adverse weather events, have shown that the effects are significant for low-input farming systems, such as subsistence farming in marginal areas and because of socio-economic, demographic and policy trends have the least capacity to adapt to changing climatic conditions (Mutekwa 2009). Climate change is a serious threat to development and poverty reduction efforts in Africa (Mugambiwa & Dzomonda 2018; Mugambiwa & Tirivangasi 2017). The continent is facing various health risks associated with climate change and threaten to reverse development efforts and subject the continent to long-term poverty.…”
Section: Introductionmentioning
confidence: 99%
“…The group noted that, given the limited capacity in this area, international assistance maybe required to develop curricula and teaching materials. Other studies in have documented considerable gaps in knowledge on climate change among university students across disciplines and the limited ability of these future leaders to engage with others on the topic [ 62 , 63 ]. Overall, the research outputs by South Africa scientists on climate change has grown (around 600 academic publications in 2015), but only 3%, or about 20, of these publications make reference to health [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lessons learned from two municipal case studies in the Western Cape, South Africa [ 44 ] South Africa Western Cape Province Case studies Semi-structured key informant interviews; documents Thematic analysis Residents of local areas To identify factors that enable action to be taken at local government level Integration of CC into other policies or plans CC adaptation plan Performance of adaptation response Role of dedicated environmental champions in political leadership. Costs of CC A normative model for integrating organisations for disaster risk reduction and climate change adaptation within SADC member states [ 69 ] Botswana, Madagascar, Malawi, Namibia, South Africa, Swaziland, Tanzania, Zambia and Zimbabwe Gauteng Mixed methods Documents, interviews, online survey Thematic analysis and triangulation Government officials To investigate the actors and their location in government that create and shape governance in disaster risk reduction and CC adaptation integration Integration of CC into other policies or plans Disaster risk reduction and CC adaptation Level of preparedness for CC-induced disasters, warning information Level of integration of government organisations Local climate governance in the Global South: the case of eThekwini Municipality and the Responsible Accommodation Campaign [ 51 ] South Africa eThekwini, KwaZulu Natal Province Case study Documents, observation of meetings and forums, key informant interviews, quantitative and qualitative questionnaires Action research project with mixed methods for data analysis Government officials, local municipal and city officials To identify different forms of local climate governance with a specific focus on relevance of networks Importance of network governance approach to impact climate governance Network governance Outcomes of policies or institutions Ability of network governance to shape climate policy and alter a project and its implementation Climate change and vulnerability discourse by students at a South African university [ 63 ] South Africa Limpopo Province Survey Self-report survey questionnaire Univariate and bivariate analysis University students To assess the knowledge and understanding of CC and its impacts by university students by faculty and gender CC knowledge U...…”
Section: Review Methodsmentioning
confidence: 99%
“…[3] Not all adolescents are equally empowered to take up these challenges, however. There are major gaps in knowledge about climate change among adolescents in many low-and middle-income countries, including SA, [4,5] and climate activism is nascent in these settings. [6] In SA there are around 10 million adolescents (10 -19 years), who make up about 20% of the country's population.…”
Section: Guest Editorialmentioning
confidence: 99%
“…After 4 years of delays, the US Supreme Court ruled that the case may proceed, [3] despite the country's Department of Justice holding that 'there is no right to a climate system capable of sustaining human life' , among other arguments. [4] While overall climate change litigation has met with mixed success, a case brought by youth in South Africa (SA) may have merit. The country has one of the most progressive constitutions in the world, and, unlike many others, it expressly sets out the right to a healthy environment.…”
Section: Youth-led Litigation Against the South African Government Anmentioning
confidence: 99%